Narrative of Obsession: Manipulated Identities, Labyrinthine Emotions in Iris Murdoch’s A Word Child - Nazila Herischian; Seyed Majid Alavi Shooshtari; Naser Motallebzadeh (Critical Literary Studies)
The theoretical discussion of the present paper is particularly based on the insights of Giorgio Agamben contextualized in Iris Murdoch’s novel, A Word Child (1975), written in the transitional period of the seventies England. It will inspect Agamben’s biopolitical insights to examine how they may contribute to understanding of the dark side of sovereignty considering the figure of a banished individual. Taking the precariousness of the emotional, political and ontological faculties of ‘love’, ‘homo sacer’ and ‘bare life’ allocated to the human being in Murdoch’s novel, A Word Child, this paper offers a different view of Murdoch’s inspirational emphatic love, socio-political abstruse problems in her novel arguing that Agamben’s account of these issues supplies an underlying structure of the form-of-life. It resounds through Agamben’s view as a never-ending struggle of human beings to underpin the messiness and cruelty of life in which characters are emotionally engaged and entrapped in order to examine some potentialities as the escape routes from the prevailing deadlocks of the era and eventually to trace, according to Agamben, a form-of-life that is called a happy life.